MicroMATER. A Proposed Standard Format for Exchanging Lexical / Terminological Data Files - Melby, Alan (Meta, 1991)
Abstract As more and more translators and terminologists use microcomputers, there will be an increased need to transfer terminology files electronically between requesters of translation and translators, between large terminology databases and users. Such exchanges could be greatly facilitated by widespread adoption of a standard intermediate format. Terminology files convened to this format would be accessible to all who use the standard, without their needing to know the details of the proprietary format from which the file was converted. MicroMATER, an application of the MATER standard, which can be used on microcomputers and mainframes alike, is proposed as a candidate to fill the need for an exchange format. It is flexible enough to accommodate a variety of record layouts and lexically-oriented files as well as concept-based terminological files. MicroMATER files can even be created in a text editor and manipulated by a shareware program available from the BYU-TRG.